Overview of the Granting of Marriage Dispensation for Minors (Study on the Determination of the Rantauprapat Religious Court Number 62/Pdt.P/2017/Pa.Rap) - Siska Wahyuni; Toni Toni (Budapest International Research and Critics University, 2022)
Marriage is something that is commanded by Allah SWT and the Messenger, in which there is wisdom, including being able to bring inner peace and prevent people from committing immorality. Underage marriages require a dispensation application submitted by the applicant/parents for a legal marriage requirement and supported by evidence of a rational application to convince the judge in giving consideration to the decision of the Religious Court. This research is based on case study normative law research by examining the Rantauprapat Religious Court Decision Number 62/Pdt.P/2017/PA.Rap. Types of Qualitative research. The results of the discussion on the dispensation of minors have the basis that they are allowed to marry in accordance with Article 7 paragraph (1) of Law no. 1 of 1974 states